15.1k views
4 votes
Given: f(x)=x^2 and g(x)=x+1 find g[f(-2)]

2 Answers

2 votes

Answer:


Explanation:


Given: f(x)=x^2 and g(x)=x+1 find g[f(-2)]-example-1
User OrderAndChaos
by
4.8k points
3 votes

Answer:

Answer: 5

Explanation:

Remark

Start with the meaning of g[f(x)]. This when you write g(x), where ever you see and x in g(x), put in an f(x)

g(f(x))

g(x)= x + 1 Substitute f(x) for x

g(f(x)) = f(x) + 1 Substitute x^2 for f(x)

g(f(x)) = x^2 + 1

g(f(-2)) = (-2)^2 + 1 Substitute -2 for x

g(f(-2)) = (4) + 1

g(f(-2)) = 5 Answer

User Jared Grubb
by
4.8k points